Mapping of Academic Procrastination and Self-trusted Public Education - Wilson Wilson; Sumardi Sumardi; Yuka Martilisda Anwika; Siti Roidah (Universitas Negeri Padang, 2021)
Academic procrastination behavior often occurs, will cause problems of lack of discipline, low motivation, and depletion of self-confidence. Self-confidence is a very important factor for students, because the attitude of self-confidence will make students feel that there is confidence in their abilities, optimism, objectivity, responsibility, rationality and reality, which then feel able or not to do academic tasks that become performance. The results of the level of self-confidence of students of the Community Education Study Program, Faculty of Education and Teacher Training, Riau University are at a moderate level. Academic procrastination of students of the community education study program, Faculty of Education and teacher training, University of Riau is at a moderate level. There is a significant relationship between self-confidence and academic procrastination of community education study program students.Keywords: Academic procrastination behavior, self-confidence,